Frequency weighted model order reduction techniques - Wan Mariam Wan Muda (Tesis University of Western Australia, 2012)
This thesis investigates the frequency weighted balanced model order reduction problem for linear time invariant systems. First, two new frequency weighted balanced truncation techniques based on zenoonossterms are proposed. Both methods are applicable for single-sided weighting, smdl are based on modifications to Sreeram and Sahlan’s technique. The first method ras.es the properties of all-pass function to transform the original frequency weighted model order reduction problem into an equivalent unweighted model reduction problem, while in the second method, the relationship between the final and the intemaediiate reduced order model used in Sreeram and Sahlan's technique is derived.